1997
DOI: 10.1017/s0963548397002976
|View full text |Cite
|
Sign up to set email alerts
|

Crossing Numbers and Hard Erdős Problems in Discrete Geometry

Abstract: We show that an old but not well-known lower bound for the crossing number of a graph yields short proofs for a number of bounds in discrete plane geometry which were considered hard before: the number of incidences among points and lines, the maximum number of unit distances among n points, the minimum number of distinct distances among n points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
242
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(246 citation statements)
references
References 21 publications
1
242
0
2
Order By: Relevance
“…We can now continue by applying the crossing lemma argument, exactly as done by Székely and in other works (e.g., see [8,13]), and conclude that…”
Section: Proof Of Propositionmentioning
confidence: 62%
See 2 more Smart Citations
“…We can now continue by applying the crossing lemma argument, exactly as done by Székely and in other works (e.g., see [8,13]), and conclude that…”
Section: Proof Of Propositionmentioning
confidence: 62%
“…This is an instance of a fairly standard point-curve incidence problem, which can be tackled using the well established machinery, such as the incidence bound of Pach and Sharir [8], or, more fundamentally, the crossing-lemma technique of Székely [13] (on which the analysis in [8] is based). However, to apply this machinery, it is essential that the curves of Γ have a constant bound on their multiplicity.…”
Section: Unit Circles Spanned By Points On Three Unit Circlesmentioning
confidence: 99%
See 1 more Smart Citation
“…This result implied an upper bound of O(n log 3 n log log n) on the running time of Efrat and Sharir's [8] segment center algorithm. Pach and Tardos [28] used the forbidden submatrix framework to obtain a new proof that there are at most O(n 4/3 ) unit distances among n points in the plane, matching the best known upper bound [31,23,32,1]. Very recently the author [30] has shown that numerous data structures based on path compression and binary search trees can be analyzed in a simple, uniform way using the forbidden submatrix method.…”
Section: Introductionmentioning
confidence: 99%
“…This result was used to deduce the best known lower bound for the number of distinct distances determined by n points in the plane [Sz95], [ST01], [KT04] and upper bound for the number of different ways how a line can split a set of 2n points into two equal parts [D98], and it has some other interesting corollaries [PS98], [PT02], [STT02], [MSSW06], [BCSV07].…”
Section: Introductionmentioning
confidence: 99%